Pengaruh Key Performance Indicator (Kpi) dan Lingkungan Kerja Terhadap Kinerja Karyawan Tazbiya Brands - Nonzha Anita; Etika Sabariah (Jurnal Riset dan Inovasi Manajemen, 2023)
In this study there are two variables that influence each other, namely the independent variable, namely the Key Performance Indicator and the Work Environment. Which affects the dependent variable, namely Tazbiya Brands Employee Performance. Research using quantitative methods with saturated sampling of 40 employees as respondents. The Key Performance Indicator variable has a t value> t table (4.216> 2.026) with a significant 0.00> 0.05 so that the Key Performance Indicator has a significant effect on employee performance. Meanwhile, the work environment variable has a t value> t table (1.958> 2.026) with a significant 0.038> 0.05 so that the work environment has a significant effect on employee performance. Key Performance Indicator and work environment simultaneously have a significant effect on employee performance. Based on the results of the above analysis, it can be concluded that the Tazbiya brands company has performance appraisal indicators that need to be considered as evaluation material so that it affects employee performance and has a good work environment in the company.